Bioactive properties of peptides obtained from Argentinian defatted soy flour protein by Corolase PP hydrolysis - Coscueta, Ezequiel R. (2017)
Enzymatic hydrolysis of soybean meal protein isolate (SPI) obtained under two temperature conditions with Corolase PP was studied, assessing the impact of hydrolysis on potential antioxidant and antihypertensive activities. The protein was isolated from soybean meal under controlled conditions of time and temperature (70 C, 1 h; 90 C, 30 min). Degree of hydrolysis assessed the progress of hydrolysis at different sampling times. For hydrolysates the antioxidant and angiotensin-converting-enzyme (ACE) inhibitory activities were measured. As observed, the DH was increasing until reaching 20% at 10 h with disappearance of globular proteins and generation of low molecular weight peptides (less than 3 kDa). A significant increase in antioxidant and ACE inhibitory capacities was observed. Five main peptides were identified, which may explain through their sequences the bioactive properties analyzed. Through this study was possible to obtain for the first time with Corolase PP soy hydrolysates with potential antioxidant and ACE inhibitory activities, which can be used to obtain new added value functional ingredients from soy meal.